Perlindungan hak tersangka pada proses penyidikan menurut HAM dalam sistem pidana Indonesia dan sistem pidana internasional - Rahmiati; Sanjaya, Sendi; Maria Tinambunan, Eva (Universitas Tangerang Raya, 2024)
Efforts to provide human rights protection, including the rights of suspects, in Indonesia are the wishes of the 1945 Constitution and statutory regulations, which mandate this. The inclusion of human rights in the police's duties as investigators is also confirmed in Article 4 of Law Number 2 of 2002 concerning the Police. So the authority of the police as investigators must pay attention to the principles contained in the Human Rights Law (HAM). In its implementation it has not run optimally, especially for those who do not understand the law. So that they do not get their rights as suspects in criminal cases. So the aim of this research is to analyze the protection of suspects' rights in the process of investigating criminal cases in the Indonesian criminal system and the international criminal system